2016
DOI: 10.1088/2053-1583/4/1/015013
|View full text |Cite
|
Sign up to set email alerts
|

Core level shifts of intercalated graphene

Abstract: Through intercalation of metals and gases the Dirac cone of graphene on Ir(111) can be shifted with respect to the Fermi level without becoming destroyed by strong hybridization. Here, we use x-ray photoelectron spectroscopy to measure the C 1s core level shift(CLS) of graphene in contact with a number of structurally well-defined intercalation layers (O, H, Eu, and Cs). By analysis of our own and additional literature data for decoupled graphene, the C 1s CLS is found to be a non-monotonic function of the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 60 publications
14
62
0
Order By: Relevance
“…The broadened peak can be well fitted with three components. The low binding energy component at 283.9 eV corresponds to pristine Gr, the dominant component at 284.1 eV is attributed to Gr weakly interacting with iron, and the small component C′ at 284.5 eV can be assigned to a stronger interacting Fe/Gr interface [30], n-doped Gr [54], or to sp 3 hybridized carbon induced by the presence of iron [55,56]. The detected presence of pristine Gr component after 1 ML Fe deposition is consistent with the expected Volmer-Weber 3D growth of Fe clusters on Gr [12].…”
Section: Thermally Induced Fe Intercalation Into the H-bng/pt(111) Inmentioning
confidence: 99%
“…The broadened peak can be well fitted with three components. The low binding energy component at 283.9 eV corresponds to pristine Gr, the dominant component at 284.1 eV is attributed to Gr weakly interacting with iron, and the small component C′ at 284.5 eV can be assigned to a stronger interacting Fe/Gr interface [30], n-doped Gr [54], or to sp 3 hybridized carbon induced by the presence of iron [55,56]. The detected presence of pristine Gr component after 1 ML Fe deposition is consistent with the expected Volmer-Weber 3D growth of Fe clusters on Gr [12].…”
Section: Thermally Induced Fe Intercalation Into the H-bng/pt(111) Inmentioning
confidence: 99%
“…This decrease of the n-doping character of the graphene layer reflects an un-doping effect with respect to the as-grown layer, evidencing that the underlying oxygen atoms decouple the graphene layer. Graphene n-doping was previously observed in graphene on iridium [ 7 , 47 ] as well as on Cu foils [ 23 , 24 , 48 ], although in our system it is lower. However, it should be noted that for the graphene on iridium, the interaction between iridium and graphene prior to intercalation is stronger than in the case of Cu.…”
Section: Resultsmentioning
confidence: 45%
“…It must be noticed that prior to the intercalation process, our graphene layer shows a non-negligible interaction with the substrate that leads to a n-doping behaviour, as previously reported [ 4 ]. The down shift in binding energy (BE) observed during this intercalating process indicates that the initial n-doping of the as-grown graphene layer diminishes upon intercalation, as described by Michely et al [ 47 ]. This decrease of the n-doping character of the graphene layer reflects an un-doping effect with respect to the as-grown layer, evidencing that the underlying oxygen atoms decouple the graphene layer.…”
Section: Resultsmentioning
confidence: 85%
“…Earlier studies have conclusively demonstrated the spectral peak structure as arising from a resonant optical transition from the pair of Rashba-split surface states of the iridium substrate to the n=1 IPS of graphene 23,49 . However, the surface states may be strongly perturbed or eradicated by the mere presence of a trace amount of stray surface oxygen adsorbates 50 . Consequently, the resonant excitation channel via the Rashba surface states is extinguished thereby quenching the resonance feature, as shown in Fig.…”
Section: Spectral Intensity Featuresmentioning
confidence: 99%
“…In this section, we use our experimentally determined work function values to obtain the work function of Gr/O/Ir. Since the oxygen intercalation typically uses partial graphene coverage 50 , the measured work function using 2PPE is an average over multiple surface domains, i.e., monolayer (ML) graphene patches. Thus in order to estimate the work function Φ Gr/O/Ir of an isolated Gr/O/Ir single domain, i.e., its local work function, we need to disentangle the multi-domain effects using prior experimental results.…”
Section: Work Function Measurement For Gr/o/irmentioning
confidence: 99%